PELAKSANAAN TAKE OVER PEMBIAYAAN DI PT. BANK SYARIAH MANDIRI CABANG MEDAN - MUHAMMAD RIZALDY (PREMISE LAW JURNAL, 2015)
The funding in Islamic Bank conducted by the principle of cooperation through profit sharing system, so that customers are not charged interest as a conventional bank. The the implementation of funding takeovers conducted in PT. Bank Syariah Mandiri Medan Branch begins with the propose of the funding take over by customers. Once approved, the Bank analyzes and then issued Affirmation Approval funding take over, followed by binding of Al-qardh ie funding agreement between PT. Bank Syariah Mandiri Medan Branch and customers to take over the funding from another bank to PT. Bank Syariah Mandiri Medan Branch, and attended the signing of Al-Murabahah agreement. The factors that lead to funding take over in PT. Bank Syariah Mandiri Medan Branch, are: first, the internal factors, namely the management policy of funding through a few things like: ease of requirements, no penalty, cheap and fixed installment every month, and promo banking. The second, external factors, namely: consideration of the advantages and benefits, which the BSM funding is done by the profit sharing system (margin), the customer wishes to practice the Islamic law, interest rates on bank previously been increased, and the presence of one and the other thing that makes the debtor disappointed. The legal consequences of the implementation of the funding take over is that the PT. Bank Syariah Mandiri Medan Branch overtake the old lender to pay the remaining debt to the creditor old customers. The implementation of the funding take over resulted in the shift of security interest over the collateral object used as collateral conducted through the roya. Keywords: take over, funding, syariah